A case report of pediatric calciphylaxis–a rare and potentially fatal under diagnosed condition. Issue 27 (July 2018) - Stârcea, Magdalena; Gavrilovici, Cristina; Elsayed, Andra; Munteanu, Mihaela; Lupu, Vasile Valeriu; Cojocaru, Elena; Miron, Ingrith; Miron, Lucian
Abstract: Rationale: Though to be rare, calcific uremic arteriolophathy (CUA) is an ectopic calcification entity causing pain and disabilities in patients with chronic renal insufficiency, thus increasing the morbidity and mortality. Patient concern: We report a case of four years old boy admitted with acute respiratory failure. Physical examination revealed: irritability, purple subcutaneous hard nodules, tachypnea, dry spasmodic cough, respiratory rate 45/min, heart rate 110/min, blood pressure 100/60 mmHg, with normal heart sounds, no murmurs, hepatomegaly with hepato-jugular reflux. He was diagnosed at 2 years old with stage 5 chronic kidney disease due to untreated posterior urethral valve, and subsequently started peritoneal dialysis. He developed severe renal osteodystrophy, refractory to standard phosphate binders. Diagnoses: Pathology examination revealed the presence of diffuse calcifications involving the skin, brain, heart, lung, kidney, stomach and pancreas, consistent with the underlying diagnosis of CUA. Intervention: Apart from standard treatment for end stage renal disease and associated co-morbidities, intensive care procedures have been initiated: oxygen therapy, continuous positive airway pressure, inotropic medication (Dopamine, Dobutamine), anticonvulsants (Diazepam), and antiedematous therapy (Dexamethasone). Outcome: His pulmonary function rapidly deteriorated up to the severe hypoxemia, seizures and cardio-respiratory arrest, despite the initiation of intensive care measures. Lessons: A careful follow up of small children might detect in time an abnormal urinary pattern. The diagnosis of growth failure should also trigger urgent further investigation.